Analytical solution to orifice design in a rotary valve controlled electro-hydraulic vibration exciter for high-frequency sinusoidal vibration waveform. (October 2019) - Wang, He; Wang, Chengwen; Quan, Long; Gong, Guofang; Li, Wenjing
The present study is focused on a novel method for the acquisition of high-frequency sinusoidal vibration waveform with electro-hydraulic vibration exciter. A rotary valve controlled electro-hydraulic vibration exciter is proposed to make it easier to obtain high vibration frequency than the conventional servo valve controlled counterpart. Three common used offices are taken into consideration: rectangular orifice, triangular orifice, and semicircular orifice. Analytical solution to orifice design of shape and axial length is suggested for the accurate control of vibration waveform. Harmonic theory borrowed from electronic technology is used as an evaluation index for the shape of vibration waveform. The orifice shape design decision is made according to the total harmonic distortion of vibration waveform. The nonlinear differential equation which models vibration waveform is established. The orifice axial length is designed according to the supply pressure, vibration frequency, and amplitude. Both theoretical and experimental results show that rectangular orifice is desirable for high-frequency sinusoidal vibration waveforms. With the orifice design solution, the proposed vibration exciter can output the vibration waveform with total harmonic distortion of less than 1% as compared with sinusoidal waveform and maximum error of 5% as compared with experimental value at vibration frequency of higher than 100 Hz, and greatly extend the frequency bandwidth when sinusoidal vibration waveform is required.